2016
DOI: 10.1177/0194599816670137
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Positioning for In‐Office Otology Procedures

Abstract: Objective Surgeons often report musculoskeletal discomfort in relation to their practice, but few understand optimal ergonomic positioning. This study aims to determine which patient position-sitting versus supine-is ergonomically optimal for performing otologic procedures. Study Design Observational study. Setting Outpatient otolaryngology clinic setting in a tertiary care facility. Subjects and Methods We observed 3 neurotologists performing a standardized simulated cerumen debridement procedure on volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…Tonsillectomies and adenoidectomies had worse ergonomics than tympanostomy tube insertions, consistent with work indicating appropriate microscope use, as used with tympanostomy tube insertion, can improve ergonomics. 19,20 Location of the tonsils and adenoids leads to compromising positions for effective visualization. Headlamp and loupe use, compared to naked-eye visualization, were significant predictors of RULA score during tonsillectomy or adenoidectomy in this study, consistent with a recent review that found that use of either in open cases is a risk factor for work-related MSK pain and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Tonsillectomies and adenoidectomies had worse ergonomics than tympanostomy tube insertions, consistent with work indicating appropriate microscope use, as used with tympanostomy tube insertion, can improve ergonomics. 19,20 Location of the tonsils and adenoids leads to compromising positions for effective visualization. Headlamp and loupe use, compared to naked-eye visualization, were significant predictors of RULA score during tonsillectomy or adenoidectomy in this study, consistent with a recent review that found that use of either in open cases is a risk factor for work-related MSK pain and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged microscopic work in particular has been linked to increased risk of neck and back strain, 6 even in the outpatient setting. 7 Most otolaryngologists report low rates of ergonomic training and demonstrate medium to high ergonomic severity risk and high levels of musculoskeletal strain when observed in the operating room. 8 In a UK survey of 325 ENTs, 72% reported back or neck pain and otologists were found to have the highest reported pain of ENT subspecialties, likely related to microscope work that can require hours of static neck, back, and hand positions.…”
Section: Discussionmentioning
confidence: 99%
“…6,21,22 Govil et al performed a comparison of providers while performing cerumen removal using the RULA to come up with specific recommendations about the ergonomic favorability of various positions; however, there remains a need to provide objective measures of ergonomically good and bad positioning during ALS. 23 Ramakrishnan and Milam similarly evaluated the ergonomics of sinus surgeons during functional endoscopic sinus surgery (FESS) and found significant fatigue reported after FESS with measurable EMG changes. 24 A recent randomized, prospective study of providers performing microsuspension laryngoscopy determined that there is demonstrable fatigue over time as shown by EMG.…”
Section: Discussionmentioning
confidence: 99%